COMMENTARY ON COMMENTARIES: A SPACE FOR DIALOGUE AMONG DIFFERENT PERSPECTIVES - Tavares, Sofia (2013)
In this commentary we discuss our reactions towards the six contributions on our article “The psychotherapist’s social role under a dialogical perspective: A study of the personal construction of «I as psychotherapist»” (in this issue). These commentaries discuss a multiplicity of problems and potentials, providing us with a meaningful space for dialogue among our multiple and sometimes discrepant perspectives. We have organized our reaction around three issues: (1) the importance of context influence on the process of being a psychotherapist; (2) the use of the motives as a tool to organize the psychotherapists’ diversity; and (3) the methodology for studying the dialogical processes.